Structural and Luminescence Properties of Silica-Based Hybrids Containing New Silylated-Diketonato Europium(III) Complex - Duarte, Adriana P. [UNESP]; Gressier, Marie; Menu, Marie-Joelle; Dexpert-Ghys, Jeannette; Caiut, Jose Mauricio A.; Ribeiro, Sidney José Lima [UNESP] (Amer Chemical Soc, 2012)
A new betadiketonate ligand displaying a trimethoxysilyl group as grafting function and a diketone moiety as complexing site (TTA-Si = 4,4,4-trifluoro-2-(3-trimethoxysilyl)propyl)-1-3-butanedione (C4H3S)COCH[(CH2)(3)Si(OCH3)(3)]COCF3) and its highly luminescent europium(III) complex [Eu(TTA-Si)(3)] have been synthesized and fully characterized. Luminescent silica-based hybrids have been prepared as well with this new complex grafted on the surface of dense silica nanoparticles (28 +/- 3 nm) or on mesoporous silica particles. The covalent bonding of Eu(TTA-Si)(3) inside the core of uniform silica nanoparticles (40 +/- 5 nm) was also achieved. Luminescence properties are discussed in relation to the europium chemical environment involved in each of the three hybrids. The general methodology proposed allowed high grafting ratios and overcame chelate release and tendency to agglomeration, and it could be applied to any silica matrix (in the core or at the surface, nanosized or not, dense or mesoporous) and therefore numerous applications such as luminescent markers and luminophors could be foreseen.